2019
DOI: 10.1152/ajpheart.00618.2018
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism of late systolic mitral valve prolapse: systolic superior shift of leaflets secondary to annular dilatation that causes papillary muscle traction

Abstract: Progressive superior shift of the mitral valve (MV) during systole is associated with abnormal papillary muscle (PM) superior shift in late systolic MV prolapse (MVP). The causal relation of these superior shifts remains unclarified. We hypothesized that the MV superior shift is related to augmented MV superiorly pushing force by systolic left ventricular pressure due to MV annular dilatation, which can be corrected by surgical MV plasty, leading to postoperative disappearance of these superior shifts. In 35 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…A previous in- vestigation on late-systolic MVP has demonstrated that a systolic LV-LA pressure gradient on larger MV leaflets/ annulus can cause greater MV superiorly pushing force ( Figure 5), shifting MV leaflets superiorly, which secondarily tract PMs to shift superiorly. 6) Secondary PM traction has been confirmed by the disappearance of PM superior shift following surgical MV annuloplasty to reduce the MV annular area and MV superiorly pushing force. 6) Such abnormal pathophysiology does not develop in patients with holo-systolic MVP and only modest MV annular dilatation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A previous in- vestigation on late-systolic MVP has demonstrated that a systolic LV-LA pressure gradient on larger MV leaflets/ annulus can cause greater MV superiorly pushing force ( Figure 5), shifting MV leaflets superiorly, which secondarily tract PMs to shift superiorly. 6) Secondary PM traction has been confirmed by the disappearance of PM superior shift following surgical MV annuloplasty to reduce the MV annular area and MV superiorly pushing force. 6) Such abnormal pathophysiology does not develop in patients with holo-systolic MVP and only modest MV annular dilatation.…”
Section: Discussionmentioning
confidence: 96%
“…6) Secondary PM traction has been confirmed by the disappearance of PM superior shift following surgical MV annuloplasty to reduce the MV annular area and MV superiorly pushing force. 6) Such abnormal pathophysiology does not develop in patients with holo-systolic MVP and only modest MV annular dilatation. Results of the present study along with those of the previous studies suggest that augmented leaflet tissue distensibility, in addition to structurally large MV annulus, suggesting primary tissue fragility and leaflet tissue elongation, may further cause abnormal superior shift of PMs and contribute to systolic MV annular expan-sion in patients with MVP.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An echocardiogram is a fundamental study required for the diagnosis of MVP with a flail leaflet and grading of mitral regurgitation (MR) severity [ 2 ]. A systolic billowing of any portion of the mitral leaflets of 2 mm or more above the annular plane in a long-axis view on echocardiogram is diagnostic for MVP [ 3 ]. MVP with a flail leaflet is a common cause of acute or sub-acute severe MR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%